A contribution to the identification of charcoal origin in Brazil III: Microscopic identification of 10 Cerrado species - Goņcalves, Thaís A. P.; Sonsin-Oliveira, Julia; Nisgoski, Silvana; Marcati, Carmen R. [UNESP]; Ballarin, Adriano W. [UNESP]; Muñiz, Graciela I. B. (CSIRO Publishing, 2018)
Brazil has one of the richest biodiversities in the world. The Brazilian savanna is a hotspot for conservation priorities and its deforestation is of global concern. Conservation in this biome is threatened by unsustainable use of forests, such as illegal logging for charcoal production. Thus, government agents need to verify whether charcoal loads follow the Document of Forestry Origin (DOF). To improve charcoal identification, our study presents the microscopic description of 10 Cerrado species and provides an identification key to aid government agents during surveillance. We analysed charcoal samples with a scanning electron microscope. The method of carbonisation simulated real conditions. We chose species with similar wood anatomy (sparse axial parenchyma and narrow rays), which increases misidentification by forest controllers because of their difficulty to identify these features. Also, paratracheal scanty, diffuse and diffuse-in-aggregates parenchyma were harder to recognise in charcoal than in wood. Other features, such as vessels, rays and abundant axial parenchyma, were easily identified. The present work can be used as a part of a charcoal anatomy database focussed on preventing deforestation in Brazil and in other countries with similar problems.
Keywords: Anatomy; Forestry supervision; Nature Conservancy